Catalysis and automotive pollution control : proceedings of the First International Symposium (CAPOC I), Brussels, September 8-11, 1986 - CAPOC; Crucq, A. (André); Frennet, A. (Alfred) (Studies in surface science and catalysis, 1987)
In June 1984 the EEC Commission proposed new standards of permissible exhaust gas from motor vehicles to be introduced in Europe; these standards were approved by the Ministers of the Environment one year later. As the control of automotive pollution is at present mainly a catalytic problem, it was decided to hold an International Symposium on the subject, and an organizing committee composed of people engaged in catalytic research in the different Belgian Universities was constituted. This was the first Symposium of its kind to be held on an international level, and the quality and scientific interest of the papers presented was exceptional. It is planned to hold a follow-up Symposium in 2 to 3 years' time.The first part of the book is a general introduction to the problem of automotive pollution. The second, properly catalytic, part is devoted to fundamental and applied studies on pollution control, with emphasis on exhaust catalytic converters.